Factors Affecting Quality of Care in Maternal and Child Health in Timor-Leste: A Scoping Review. (July 2022) - Khorshed, Mahmuda Shayema; Lindsay, David; McAuliffe, Marie; West, Caryn; Wild, Kayli
Timor-Leste faces many challenges implementing quality maternal, newborn and child health (MNCH) services due to resource constraints and socio-cultural factors that disproportionately affect the health of women and children. A scoping review was conducted to map the quality of MNCH services against WHO quality standards on: 1. Provision of care, 2. Experiences of care, and 3. Cross-cutting standards. The literature search identified 1058 citations, from which 28 full-text articles met the inclusion criteria. The findings highlight health workers' limited capacity to provide quality services and referrals. The major reasons for this are: a lack of essential supplies, poor infrastructure and transport, limited opportunities for ongoing learning, and gaps in health information systems. Provision of care standards and cross-cutting standards require attention at a broad systems level. Findings related to experiences of care highlight the importance of effective communication, respect, and emotional support, particularly for vulnerable women and children who have difficulty accessing services, and for those who have experienced violence. These experience-related standards could be addressed at an individual health worker and health service level, as well as at a systems level. This review provides direction to focus quality-improvement initiatives within local health facilities, as well as at municipal and national level.